Minnesota : a history of the state - Blegen, Theodore Christian, 1891-1969 (University of Minnesota Press, 1975)
A concise yet comprehensive account of the state's development, following the progress and landmarks in politics, technology, the arts, architecture and more. It deals with the earliest stuggles of the fur traders to the modern problems of urban transportation. The second edition includes a concluding a chapter by Russell W. Fridley.